Review on Clustering Mechanism For Web Based Data Mining - *, Ritu; Kumar, Mahesh (IJRDO -Journal of Computer Science Engineering, 2017)
K-Means Clustering algorithm is need to classify given data set into K clusters; value of K is defined by user which is fixed. In this first centroid of each cluster is selected for clustering & then according to chosen centriod, data points having minimum distance from given cluster, is assigned to that particular cluster